Besnoitia besnoiti-induced neutrophil clustering and neutrophil extracellular trap formation depend on P2X1 purinergic receptor signaling - Espinosa, Gabriel; Conejeros, Iván; Rojas-Barón, Lisbeth; Hermosilla, Carlos Rodrigo; Taubert, Anja (Frontiers in Immunology, 2023)
Bovine besnoitiosis is a re-emerging cattle disease caused by the cyst-forming apicomplexan parasite Besnoitia besnoiti. Neutrophil extracellular trap (NET) formation represents an efficient innate immune mechanism of polymorphonuclear neutrophils (PMN) against apicomplexan parasites, including B. besnoiti. PMN purinergic signaling was proposed as a critical factor for NET formation. One important purinergic ligand is ATP, which is recognized as a danger signal and released into the extracellular space acting as an autocrine/paracrine signaling molecule. ATP-driven effects on PMN via the nucleotide P2 receptor family include chemotaxis, reactive oxygen species (ROS) production, and NET formation. So far, data on both PMN ATP concentrations and the role of ATP as a key modulator of purinergic signaling in B. besnoiti tachyzoite-triggered bovine NETosis is scarce. Current data showed that B. besnoiti tachyzoite exposure to bovine PMN neither changed total PMN ATP nor extracellular ATP quantities even though it significantly triggered NET formation. Moreover, B. besnoiti tachyzoite-exposed PMN revealed enhanced oxygen consumption rates (OCR) as quantified by the Seahorse metabolic analyzer. Exogenous supplementation of ATP or non-hydrolizable ATP (ATPγS) led to increased extracellular acidification rates (ECAR) but failed to alter tachyzoite-induced oxidative responses (OCR) in exposed PMN. In addition, exogenous supplementation of ATPγS, but not of ATP, boosted B. besnoiti tachyzoite-induced anchored NET formation. Referring to purinergic signaling, B. besnoiti tachyzoite-triggered anchored NET formation revealed P2X1 purinergic as receptor-dependent since it was blocked by the P2X1 inhibitor NF449 at an IC50 of 1.27 µM. In contrast, antagonists of P2Y2, P2Y6, P2X4, and P2X7 purinergic receptors all failed to affect parasite-driven NETosis. As an interesting finding, we additionally observed that B. besnoiti tachyzoite exposure induced PMN clustering in a P2X1-dependent manner. Thus, we identified P2X1 purinergic receptor as a pivotal molecule for both B. besnoiti tachyzoite-induced PMN clustering and anchored NET formation.